Growing Fit: Georgia's Model for Engaging Early Care Environments in Preventing Childhood Obesity - Kelsey McDavid; Catalina Piedrahita; Emily Vall; Christi Kay; Jean O'Connor (Georgia Southern University, 2016)
Background: In the United States, one in three children is overweight or obese by their fifth birthday. In Georgia, 35 percent of children are overweight or obese. Contrary to popular belief, children who are overweight or obese are unlikely to outgrow their weight status as adults, making early childhood an essential time to address weight status. An estimated 380,000 Georgia children attend early care and education environments, such as licensed child care centers, Head Start, and pre-kindergarten programs, which provide an opportunity to reach large numbers of children, including those at risk for obesity and overweight. Methods: To address this opportunity, the Georgia Department of Public Health, Georgia Shape - the Governor's Initiative to prevent childhood obesity, and HealthMPowers, Inc., created the Growing Fit training and toolkit to assist early childhood educators in creating policy, systems, and environmental changes that support good nutrition and physical activity. This report, the first related to this project, describes the training and its dissemination between January and December 2015. Results: A total of 103 early childcare educators from 39 early childcare education centers (22 individual childcare systems) from 19 counties in Georgia were trained. Fifteen systems completed a pre and post-test assessment of their system, demonstrating slight improvements. Training for an additional 125 early childcare education centers is planned for 2016. Conclusions: Lessons learned from the first year of the training include the need for more robust assessment of adoption and implementation of policy, systems, and environmental changes in trained centers.